PENGARUH KONSEP DIRI DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN OTOMATISASI DAN TATA KELOLA KEUANGAN - Trio Gunawan; Ciciclia Dyah Sulistyaningrum I; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The research was to find out there is or not: 1) the effect of self concept towards learning achievement on automation and finance administration; 2) the effect of self-motivated learning towards learning achievement on automation and finance administration; 3) the effect of self concept and self-motivated learning towards learning achievement on automation and finance administration.This research used quantitative research with a correlational research design. The population in this research were all students of class XI Automation and Office Administration at SMK Negeri 1 Klaten in the academic year 2018/2019 which amounted to 108 students. The sample in this research taken with proportional random sampling technique which amounted to 84 students. Data source from teacher and students. The data collection technique used questionnaire and documentation. The data analysis technique used multiple linear regression analysis with the help of IBM SPSS 23.0 program. The result of research showed that 1) there was a significant positive effect of self concept toward learning achievement on automation and finance administraiton (tcount = 4,4801, sign < 0,05); 2) there was a significant positive effect of self-motivated learning toward learning achievement on automation and finance administration (tcount = 4,326, sign < 0,05); 3) there was a significant positive effect of self concept and self-motivated learning toward learning achievement on automation and finance administration (Fcount = 48,654, sign < 0,05). This result of research showed the amount of effective contribution together equal to 54,6% and the rest still 45,4% which effected by other variables which not entered in this research.